2020
DOI: 10.1111/tpj.14621
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a significant role of glutathione reductase in the sulfur assimilation pathway

Abstract: With the objective of studying the role of glutathione reductase (GR) in the accumulation of cysteine and methionine, we generated transgenic tobacco and Arabidopsis lines overexpressing the cytosolic AtGR1 and the plastidic AtGR2 genes. The transgenic plants had higher contents of cysteine and glutathione. To understand why cysteine levels increased in these plants, we also used gr1 and gr2 mutants. The results showed that the transgenic plants have higher levels of sulfite, cysteine, glutathione and methioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…In addition, GSH is also a positive regulator of the second step of sulphate reduction since it serves as an electron donor for adenosine phosphosulphate reductase (APSR), the second enzyme of this pathway. GR, ensuring the regeneration of GSH from glutathione disulphide (GSSG), is involved in the control of sulphate reduction as demonstrated in transgenic and mutant Arabidopsis lines having increased and decreased levels of downstream metabolites (sulphite, cysteine and GSH), respectively (Cohen et al 2020). Far‐red light increased the expression of the genes encoding APSR, gamma‐glutamylcysteine synthetase and GR and the amount of GSH and reduced the level of GSSG compared to blue light as observed in barley (Balogh et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GSH is also a positive regulator of the second step of sulphate reduction since it serves as an electron donor for adenosine phosphosulphate reductase (APSR), the second enzyme of this pathway. GR, ensuring the regeneration of GSH from glutathione disulphide (GSSG), is involved in the control of sulphate reduction as demonstrated in transgenic and mutant Arabidopsis lines having increased and decreased levels of downstream metabolites (sulphite, cysteine and GSH), respectively (Cohen et al 2020). Far‐red light increased the expression of the genes encoding APSR, gamma‐glutamylcysteine synthetase and GR and the amount of GSH and reduced the level of GSSG compared to blue light as observed in barley (Balogh et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no evidence of SAT regulation by phosphorylation in Arabidopsis, the chloroplast cyclophilin CYP20-3 participates in folding of AtSAT1 in a redox-dependent fashion, to enhance the activity of AtSAT1 and to affect thiol contents (Dominguez-Solis et al, 2008). Additionally, it was recently shown that the availability of (reduced) GSH in Arabidopsis and tobacco positively affects S-assimilation downstream of APR activity, including the steady state concentration of cysteine and methionine (Cohen et al, 2020). The data presented in this study support that redox regulation of sulfate assimilation and cysteine synthesis also occurs in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfur is an essential macronutrient very important for the growth and function of plants (Zenda et al 2021). For example, sulfur treatment can reduce the accumulation of heavy metals in plants and improve stress resistance (Cao et al 2023), and sulfur deficiency will lead to growth and yield decline (Cohen et al 2020, Narayan et al 2022, Cao et al 2023). But its role in single‐cell development (e.g., trichome cell, root hair) is unknown.…”
Section: Introductionmentioning
confidence: 99%